EFEKTIVITAS PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN PROBING PROMPTING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Marlena Marlena; Fransiskus Gatot Iman Santoso (Universitas Katolik Widya Mandala Surabaya Kampus Kota Madiun, 2016)
This study is aims to find out the differences of the students’ critical thinking ability by using probing prompting approach and the students’ critical thinking ability by using direct learning. Moreover, the research is an apparent experimental quantitative research. The research conducted in the first semester of 2015/2016 at SMP Negeri 4 Madiun. The population is all the students of 7th grade. In this case, the sample of research are all students of 7th – H grade as experimental class that use probing prompting approach and also all students of 7th – I grade as control class taught by using direct learning. Further more, test method was applied as technique of data collecting. To get the sample, cluster random sampling is used in this research. The instrument used in test method was mathematic critical thinking ability test. It was applied to figure out the students’ mathematic critical thinking ability. However, the instrument of research was validated first before being tried out. Hypothesis testing applies t experiment with the real level is 0,05. Besides, hypothesis testing related to students’ critical thinking ability shows that tcounted (=0,285) is lower than ttable (=1,672). As a result, H0 is approved. In other words, there are no differences between the students’ critical thinking ability taught by using probing prompting approach and the students’ critical thinking ability taught by using direct learning. Keywords: Probing Prompting Approach, Mathematic Critical Thinking Ability.